2005
DOI: 10.1073/pnas.0408171102
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploid neurons are functionally active and integrated into brain circuitry

Abstract: The existence of aneuploid cells within the mammalian brain has suggested the influence of genetic mosaicism on normal neural circuitry. However, aneuploid cells might instead be glia, nonneural, or dying cells, which are irrelevant to direct neuronal signaling. Combining retrograde labeling with FISH for chromosome-specific loci, distantly labeled aneuploid neurons were observed in expected anatomical projection areas. Coincident labeling for immediate early gene expression indicated that these aneuploid neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 28 publications
2
130
0
Order By: Relevance
“…Several possibilities can be envisioned and are the subject of current investigations. For example, the process of mitotic spindle malformation/disruption and consequent chromosome missegregation in neural stem cells could trigger a cell cycle checkpoint that leads to apoptosis and/or reduced neurogenesis, although recent work in mice suggests that aneuploid neurons survive and function well [19]. Also, the evident PS-induced disruption of the microtubule network indicates that PS overexpression or mutation likely interferes with microtubule formation or function, possibly through an effect on microtubule associated proteins such as Tau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several possibilities can be envisioned and are the subject of current investigations. For example, the process of mitotic spindle malformation/disruption and consequent chromosome missegregation in neural stem cells could trigger a cell cycle checkpoint that leads to apoptosis and/or reduced neurogenesis, although recent work in mice suggests that aneuploid neurons survive and function well [19]. Also, the evident PS-induced disruption of the microtubule network indicates that PS overexpression or mutation likely interferes with microtubule formation or function, possibly through an effect on microtubule associated proteins such as Tau.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, age itself is the greatest risk factor for developing AD, and low levels of aneuploidy have also been shown to develop in mature brain neurons because of mitotic defects in neural precursor cells [19,34,51]. The fact that chromosome segregation defects underlie another disease of aging-cancer [4]-suggests that perhaps microtubule disfunction leading to different degrees and types of aneuploidy underlie many manifestations of "normal" aging in addition to predisposing to Alzheimer's disease when chromosome 21 is affected [32].…”
Section: Discussionmentioning
confidence: 99%
“…This failure is significant but does not necessarily reflect lower reprogrammability of neurons. Instead, the fact that an unknown proportion of functional adult neurons are aneuploid (Kingsbury et al, 2005) may account for their apparent loss of totipotency after NT. If this was indeed the reason, the data could not be interpreted in light of the high differentiation-low reprogrammability hypothesis since genetic errors are unlikely to be reversible by reprogramming.…”
Section: Somatic Cellsmentioning
confidence: 99%
“…Subsequent studies using FISH indicated that approximately 20% of adult mouse and human brain cells were aneuploid (16)(17)(18)(19)(20). These aneuploid cells were believed to arise from chromosome mis-segregation events in neural progenitor cells and were shown to integrate into brain circuitry (21,22). These high levels of aneuploidy were proposed to provide the brain with its notable phenotypic diversity while simultaneously predisposing the organ to neurodegeneration (23)(24)(25)(26).…”
mentioning
confidence: 99%